Conformal coating of CdS onto flexible enokitake-like standing gold nanowire arrays for omnidirectional low-light-intensity photocatalysis. (April 2023) - Yong, Zijun; Gong, Shu; Chesman, Anthony S.R.; Shi, Qianqian; Yap, Lim Wei; Hora, Yvonne; Fu, Runfang; Lin, Fenge; Cheng, Wenlong
Abstract: Nature's photocatalysis system is typically flexible and can function with omnidirectional sunlight illumination (e.g. plant leaves), sometimes even under low-intensity sunlight conditions (e.g. seagrass). Previous research efforts have been mainly directed at designing photocatalysts in solutions or on rigid substrates with the aim of achieving high efficiency rather than mimicking the features of ubiquitous natural biosystems. Here we report on flexible artificial leaves by using elastomer-bonded, CdS-coated, enokitake-like gold nanowire (AuNW) arrays, which can perform model chemical reactions under omnidirectional light illumination and at a low light intensity of ∼1.2 mW/cm 2 – about 1% of the sunlight energy at the sea surface level, which corresponds to the disphotic zone in the sea. The key attributes of our photocatalytic system include: (1) closely-packed, vertically aligned AuNWs offering high surface area and efficient light absorption; (2) the conformal and tunable deposition of CdS onto AuNWs enabling optimization of photocatalytic efficiency; (3) free-standing and flexible features allowing for a versatile design that mimics Nature's photocatalytic process. Graphical Abstract: ga1 Highlights: CdS can be deposited conformally to the vertically aligned gold nanowires (AuNWs). The CdS@AuNWs-based thin, soft and stretchable artificial leave is designed and fabricated. the artificial leave can function under omnidirectional light illumination and at a low light intensity of ∼1.2 mW/.